Estimates of genetic parameters for grain yield, agro-morphological traits and quality attributes in bread wheat (Triticum aestivum) - KUMAR, DINESH; KERKHI, S A; SINGH, GYANENDRA; SINGH, JANG BAHADUR (The Indian Journal of Agricultural Sciences, 2015)
A study for estimating genetic parameters was carried out by involving 10 parents and their 45 F1's planted in randomized block design (RBD) having three replications revealed significant variance for all the characters under study. The analysis of genetic components showed that significant additive and dominant components for all the traits. Positive and significant value of "F" for yield and quality components in F1 crosses indicated the preponderance of dominant and positive genes in the parents. The estimates of h2 were found highly significant for number of productive tillers/ plant, flag leaf area, spike length, spikelets/ spike, biological yield/ plant, grain yield/ plant, harvest index, ash content and gluten content, whereas, non-significant values were reported for rest of the traits. The value of (H2/4H1) for all the traits indicated the asymmetrical distribution of positive and negative alleles among the parents. The proportion of dominant and recessive genes indicated presence of dominant alleles in the parents for these traits. The ratio of h2/H21 generation revealed that more than one major gene group was responsible for controlling these traits. Estimates of SCA effects revealed that the best cross combinations namely; DBW 58/ HD 2687, DBW 58/ DBW 17, PBW 590/HD 2687, PBW 373/DBW 17, PBW 373/RAJ 3765, HD 2687/WH 711, MP 1236/PBW 373, MP 1236/HD 2687, MP 1236/PBW 590, PBW 550/HD 2687 and PBW 550/DBW 17 for respective yield components and quality traits may be exploited through heterosis breeding programme to improve these traits in wheat (Triticum aestivum L.). It may be concluded from the present investigation that these parental lines can be used as donors for improving both components in future by following bi-parental mating and diallel selective mating system could be the best breeding method in early segregating generations for improvement in these traits.